Utilisation of crumb tire rubber in development of sustainable metakaolin based high strength concrete. (22nd August 2022) - Singh Sidhu, Amandeep; Siddique, Rafat
Graphical abstract: Highlights: Compressive strength more than 60 MPa is feasible with 20% crumb rubber in HSC. Improved compressive toughness in metakaolin based HSC with crumb tire rubber. Loss of modulus of elasticity in metakaolin based HSC including crumb rubber. SonReb method can be used to estimate compressive strength for crumb rubber HSC. Abstract: Environmental protection necessitates induction of 3R (recycle, reuse, reduce) principle into the construction sector. The study investigated fresh, strength properties, and SEM/XRD analysis of high strength concrete containing 15% metakaolin and crumb rubber up to 30% as sand replacement upto 90 days. SonReb method was used to determine relationship of Ultrasonic Pulse Velocity and Rebound Hammer tests with compressive strength. Results indicate loss of workability, density, compressive strength, split tensile strength and modulus of elasticity but improved ductility at 20% crumb rubber replacement which depicted highest toughness index. Equation derived from SonReb method predicted compressive strength with reliable accuracy.